Changing Mangalehen Tuor Tradition in Mandailing Weddings: A Case Study from Damuli Pekan Village for Sociology Learning - Anggi Pratiwi; Ponidi Ponidi (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study investigates the evolving practice of the Mangalehen Tuor tradition in Mandailing wedding ceremonies, particularly in Damuli Pekan Village, and its potential as a source of contextual sociology learning. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis involving traditional leaders and indigenous Mandailing community members. Data were analyzed through reduction stages, presentation, verification, and conclusion. The findings reveal significant transformations in the tradition, particularly in the quantity and types of tuor offered, and in the dynamics of the negotiation process. Historically grounded in customary values and kinship relations, the Mangalehen Tuor tradition has shifted toward more pragmatic considerations influenced by economic factors and modern lifestyles. These shifts reflect broader processes of social change, modernization, and the influence of globalization on local cultural practices. This transformation offers valuable insights for sociological inquiry, particularly regarding adapting traditions in response to contemporary societal pressures. As such, the case of Mangalehen Tuor provides a relevant and culturally rich resource for sociology education, enabling students to examine the interplay between tradition and modernity critically. This case study contributes to a deeper understanding of socio-cultural transformation and its pedagogical implications for contextualizing sociology education. It also underscores the importance of preserving local wisdom amid global influences, offering a pathway for younger generations to engage with and learn from their cultural heritage.